Crystal structure of Aspergillus fumigatus AroH, an aromatic amino acid aminotransferase. Issue 2 (16th September 2021) - Spizzichino, Sharon; Pampalone, Gioena; Dindo, Mirco; Bruno, Agostino; Romani, Luigina; Cutruzzolà, Francesca; Zelante, Teresa; Pieroni, Marco; Cellini, Barbara; Giardina, Giorgio
Abstract: Aspergillus fumigatus is a saprophytic ubiquitous fungus whose spores can trigger reactions such as allergic bronchopulmonary aspergillosis or the fatal invasive pulmonary aspergillosis. To survive in the lungs, the fungus must adapt to a hypoxic and nutritionally restrictive environment, exploiting the limited availability of aromatic amino acids (AAAs) in the best possible way, as mammals do not synthesize them. A key enzyme for AAAs catabolism in A. fumigatus is AroH, a pyridoxal 5′‐phosphate‐dependent aromatic aminotransferase. AroH was recently shown to display a broad substrate specificity, accepting L‐kynurenine and α‐aminoadipate as amino donors besides AAAs. Given its pivotal role in the adaptability of the fungus to nutrient conditions, AroH represents a potential target for the development of innovative therapies against A. fumigatus ‐related diseases. We have solved the crystal structure of Af‐ AroH at 2.4 Å resolution and gained new insight into the dynamics of the enzyme's active site, which appears to be crucial for the design of inhibitors. The conformational plasticity of the active site pocket is probably linked to the wide substrate specificity of AroH.